Angle of repose - Stegner, Wallace 1909-1993 (Penguin, 2006)
Stegner's Pulitzer Prize-winning novel is the story of four generations in the life of an American family. A wheelchair-bound retired historian embarks on a monumental quest: to come to know his grandparents, now long dead. The unfolding drama of the story of the American West sets the tone for Stegner's masterpiece.
Keywords: Adultery -- Fiction; Domestic fiction.; Grandparents -- Fiction; Historians -- Fiction; Married people -- Fiction; Older people -- Fiction; People with disabilities -- Fiction; California -- Fiction; Fiktionale Darstellung; Domestic fiction